Design and development of mobile augmented reality for physics experiment - Abu Bakar, Juliana Aida; Gopalan, Valarmathie; Zulkifli, Abdul Nasir; Alwi, Asmidah (Springer, 2018)
Augmented Reality (AR) provides an authentic and realistic learning experience.It is obvious that younger generation prefers technology intervened learning rather than conventional learning. Although previous work on AR have shed some lights on the use of such technology on learning, studies focusing on science experiment practices are still lacking.Experiments are crucial for students to enhance critical understanding of science phenomena.This article discusses the process of designing and developing a mobile app for physics experiment using AR technology.This is an auxiliary learning tool for upper secondary school students.The aim of this Mobile AR app for Physics experiment (MARPEX) is to provide rigorous information beyond conventional experiment practices and additional learning materials. Several experiments have been selected to be included in MARPEX.An expert review is conducted to gauge feedback and recommendations. Future work includes user evaluation of MARPEX on real classroom settings.